Risk factors in cases of known deaths of young people with experience of care: an explanatory study - Craig Cowan (Scottish Journal of Residential Child Care)
This paper discusses the issue of suicidal behaviour among young people with experience of care, through an identification of suicidal behaviour risk indicators.